IMPLEMENTATION RECONSTRUCTION OF SHARING PROFIT AND LOSSES IN MURABAHAH FINANCING IN SHARIA BANK INDONESIA BASED ON ISLAMIC JUSTICE PERSPECTIVE - ahmad supriyadi (UNISSULA, 2017)
Sharia Bank is a bank that has a special characteristic in its operations by applying the principles of sharia. It shares the benefits and losses both in fund raising and murabahah financing and in service products. However, in its implementation, Sharia Bank has not yet applied the distribution of profit and loss in murabahah financing based on justice. Sharia Bank in finance products apply a lot of buying and selling principles of murabahah, which means the practice is the same as interest in conventional Banks. Murabahah financing implementation illustrates a severe problem in sharia banking law in Indonesia, it is about injustice.